First-principles investigation of the interface magnetic anisotropy of Fe/SrTiO3. (4th January 2019) - Wei, Yue; Sun, Yu-Yun; Yang, Jing; Gong, Shi-Jing; Meng, Yu-Hua; Duan, Chun-Gang
Abstract: Interface effects in magnetic nanostructures play a critical role in the magnetic properties. By using first-principles density functional theory calculations, we investigate the electronic and magnetic properties of Fe/SrTiO3 interfaces, in which both the nonpolar surface SrTiO3 (0 0 1) and the polar surface SrTiO3 (1 1 0) are considered. A particular emphasis is placed on the magnetic anisotropy energy (MAE). Comparing MAE of the Fe/SrTiO3 interfaces and the corresponding Fe monolayers, we find the Fe/SrTiO3 (0 0 1) interface decreases MAE, while the Fe/SrTiO3 (1 1 0) interface increases MAE. The interface orbital hybridization and orbital magnetic moments are analyzed in detail to understand the different interface magnetic anisotropy. Our investigation indicates that interface engineering can be an effective way to modulate the magnetic properties.